2019
DOI: 10.1007/s12186-019-09226-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Learning at Work: a Literature Review

Abstract: The research elaborating emotions in organizational settings has increased considerably in recent years. However, we lack a comprehensive understanding of the role of emotions in learning at work. This review aimed to elaborate how emotions and learning are understood in the field of workplace studies, and how emotions and learning at work are related. For the review, 31 scientific articles were selected and analysed. We found that emotions and learning were understood in a range of ways in the articles. Emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…We found that first affective and then cognitive error responses sequentially mediate this well-established relationship, laying the framework for future studies seeking to understand how learning from error climate influences engagement in social learning activities. Second, this study addresses calls for future research that investigate the role of emotions in learning (from errors) at work by highlighting the need to differentiate between individual and social learning activities in relation to error strain (Böhnke and Thiel, 2019; Hökkä et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We found that first affective and then cognitive error responses sequentially mediate this well-established relationship, laying the framework for future studies seeking to understand how learning from error climate influences engagement in social learning activities. Second, this study addresses calls for future research that investigate the role of emotions in learning (from errors) at work by highlighting the need to differentiate between individual and social learning activities in relation to error strain (Böhnke and Thiel, 2019; Hökkä et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The sentiments of the students play a substantial part in boosting their motivation and learning (Graesser & D'Mello, 2012;Hökkä et al, 2019;Pekrun et al, 2002;Trevors et al, 2017). Past studies related to the sentiments of the students have majorly focused on their apprehension while taking a test.…”
Section: Introductionmentioning
confidence: 99%
“…Students' emotions play a significant role in their motivation and learning process (Graesser & D'Mello, 2012;Hökkä, Vähäsantanen, & Paloniemi, 2019;Pekrun et al, 2002;Trevors et al, 2017). Previous research involving students' emotions have concentrated on their test-taking anxiety.…”
Section: Introductionmentioning
confidence: 99%